Combined rough and finish machining of Ti–6Al–4V alloy by electrochemical mill-grinding. Issue 4 (3rd July 2020) - Niu, Shen; Qu, Ningsong; Yue, Xiaokang; Liu, Gangqiang; Li, Hansong
Abstract: This study proposes a combined method for the electrochemical mill-grinding of Ti–6Al–4V alloy to achieve a high material removal rate, high machining accuracy and good surface quality based on rough and finish machining. In the rough machining stage, a maximum feed rate of 2.7 mm min −1 and a material removal rate of 248.3 mm 3 min −1 were achieved experimentally at a 10 mm cut depth using an abrasive tool with five rows of tool-sidewall outlet holes. In the finish machining stage, there were almost no overcuts or stray corrosions produced. The sidewall surface roughness and sidewall flatness were Ra = 1.06 and 76.8 μm after the finishing stage, which represent a 68% and 79.2% improvement compared with the rough machining stage, respectively. Finally, we fabricated a 1-mm-thick thin-walled structure using the combined machining operations, in which approximately 96% of the total material removal volume was performed at the rough machining stage.